Dopaminergic tone persistently regulates voltage-gated ion current densities through the D1R-PKA axis, RNA polymerase II transcription, RNAi, mTORC1, and translation - Krenz, Wulf-Dieter C.; Parker, Anna R.; Rodgers, Edmund W.; Baro, Deborah J. (Frontiers in Cellular Neuroscience, 2014)
Long-term intrinsic and synaptic plasticity must be coordinated to ensure stability and flexibility in neuronal circuits. Coordination might be achieved through shared transduction components. Dopamine (DA) is a well-established participant in many forms of long-term synaptic plasticity. Recent work indicates that DA is also involved in both activity-dependent and -independent forms of long-term intrinsic plasticity. We previously examined DA-enabled long-term intrinsic plasticity in a single identified neuron. The lateral pyloric (LP) neuron is a component of the pyloric network in the crustacean stomatogastric nervous system (STNS). LP expresses type 1 DA receptors (D1Rs). A 1hr bath application of 5nM DA followed by washout produced a significant increase in the maximal conductance (Gmax) of the LP transient potassium current (IA) that peaked ~4hr after the start of DA application; furthermore, if a change in neuronal activity accompanied the DA application, then a persistent increase in the LP hyperpolarization activated current (Ih) was also observed. Here, we repeated these experiments with pharmacological and peptide inhibitors to determine the cellular processes and signaling proteins involved. We discovered that the persistent, DA-induced activity-independent (IA) and activity-dependent (Ih) changes in ionic conductances depended upon many of the same elements that enable long-term synaptic plasticity, including: the D1R-protein kinase A (PKA) axis, RNA polymerase II transcription, RNA interference (RNAi), and mechanistic target of rapamycin (mTOR)-dependent translation. We interpret the data to mean that increasing the tonic DA concentration enhances expression of a microRNA(s) (miRs), resulting in increased cap-dependent translation of an unidentified protein(s).